The effect of motivational interviewing techniques on the knowledge level of asthma control among mothers of children with allergic asthma (vol 78, pg 44, 2024) - Karhan, Esra Rusen; Soylar, Pinar (Elsevier Science Inc, 2025)
[Abstract Not Available]